White matter integrity is associated with self‐awareness of financial decision‐making in cognitively healthy older adults. (December 2021) - Sunderaraman, Preeti; Gazes, Yunglin; Ortiz, Gema; Chapman, Silvia; Joyce, Jillian L.; Langfield, Christopher; Mensing, Ashley; Stern, Yaakov; Cosentino, Stephanie
Abstract: Background: Reduced awareness of one's financial decision‐making abilities (financial awareness) can result in costly financial mistakes (e.g., forgetting to pay credit card dues) and increase one's vulnerability to financial exploitation (e.g., getting scammed). In cognitively healthy older adults, thinner right medial temporal cortex is associated with overconfidence in one's financial decision‐making abilities. However, it is important to examine other neuroimaging metrics to create a comprehensive picture of the links between brain and financial awareness in healthy older adults. In the current study, we examined the white matter correlates of financial awareness and hypothesized that the tracts connecting the right temporal‐frontal regions would be most strongly correlated with financial awareness. Method: Design ‐ Cross‐sectional, prospective study. Setting ‐ Community‐based. Participants: 44 individuals were included with mean age=68.43 years (SD=5.1), mean education=15.88 (SD=2.41), 60% = women, 67% = White, 30% = Black and 3% = other races, and 95% = non‐Hispanics. Measures: Awareness Metrics – Financial awareness was measured by integrating metacognitive ratings into the Objective Financial Competency Assessment Inventory. Before each item, we obtained confidence ratings regarding performance on that item. Level of awareness was operationalized via a calibration score reflecting the difference between average performance and average confidence, reflecting the extent to which individuals were over‐ or under‐confident. Mean Diffusivity – Data were processed with Tracts Constrained by Underlying Anatomy toolbox distributed as part of the FreeSurfer library (v5.3) which produced averages of mean diffusivity for 18 white matter tracts. Lower mean diffusivity values indicated higher white matter integrity. Result: The right superior longitudinal fasciculus–temporal ( r = 0.437, p = 0.003) and parietal ( r = 0.433, p = 0.003) bundles had the strongest correlations with calibration scores such that higher (i.e., worse) diffusivity was associated with values reflecting over‐confidence. Conclusion: Our findings converge with the growing literature on the unique role of the right hemisphere temporal connections in supporting financial awareness. We find an equally important role for right parietal‐frontal connections in financial awareness. Our findings are in line with studies on financial exploitation in which the right parietal and temporal pathways were found to be involved in scam susceptibility.